Pharmaceutical dispensing - Nand, Pratibha; Khar, Roop K. (New Delhi CBS Publishers & Distributers, 1995)
The role of dispensing pharmacy has undergone tremendous changes in last few decades. In order to match the need of the hour, various universities have changed their syllabi to satisfy the new requirements. Many are in the process of doing do. Similarly at the Diploma Pharmacy level Pharmacy Council of India has come up with new regulations which have been made effective throughout the country. First three chapters deal with basics in dispensing pharmacy like prescription, incompatibilities and posology. Following five chapters from 4th to 8th describe various common dosage forms in dispensing practice. Ninth chapter discusses various commonly used cosmetic formulations. The tenth and eleventh chapters go through various aspects of sterile dosage forms and ophthalmic products. A brief introduction and formulation aspects of tablets and capsules have been dealt with in chapters 12 and 13. To assist the students and the teachers alike, there are various appendices which deal with common topics like drug interactions, pharmaceutical calculations, revision questions and patent and proprietary products.
Keywords: DISPENSING PHARMACY; PHARMACEUTICS